"Imaginings": Reflections on Plurilingual Students' Creative Multimodal Works. Issue 3 (15th September 2015) - Stille, Saskia; Prasad, Gail
Abstract : The purpose of this article is to illustrate the potential contribution of a multimodal approach to English language teaching and learning in the educational context. Collaborating with English as a second language (ESL) and classroom teachers to explore ways to improve pedagogy in multilingual, multicultural schools, the authors discovered many teachers who used the creation of multimodal texts as a core instructional strategy to go beyond basic approaches to language teaching and learning. In particular, these teachers used the creation of multimodal identity texts (Cummins & Early, 2011) as a means to involve students in producing work that was culturally relevant, socially significant, and personally meaningful. To illustrate these possibilities, the article draws on examples of student‐ and teacher‐created multimodal texts that were showcased at a regional conference for ESL teachers in Ontario in 2012 and 2014. Through interviews with students and teachers, the authors found that students actively used multimodal resources to represent and articulate personal narratives of themselves, their communities, and their language learning experiences. These narratives reflect students not only as language learners but also, more powerfully, as plurilingual subjects with voice and agency. The authors conclude by reflecting on the potential for plurilingual multimodal production in the English language classroom as a form of teaching for social justice.